"Talaqqi" in the age of bureaucracy; Symbiosis of pedagogical cultures in West Javanese "pesantren" - Millie, Julian (Wacana, Journal of the Humanities of Indonesia, 2025)
Since Indonesian independence, the Republic’s Ministry of Religion has steadily become more deeply involved in the overseeing and monitoring of the country’s internally diverse system of Islamic education. This involvement has changed the pedagogical texture of Islamic education. The bureaucratized education system of the modern nation state aims to achieve policy goals such as quality at scale, equality of access, and standardization of curricula and teacher qualifications. In contrast, many Islamic institutions, and especially the pesantren (Islamic boarding school), structure their pedagogy around spiritual and genealogical hierarchies, and maintain teaching methods that affirm those hierarchies. This research asks about the effects upon Islamic education of the standardization brought by the national education policy. Analysis focusses upon a fundamental aspect of pesantren education: the face-to-face conveyance of knowledge (Arabic: talaqqi). This pedagogy is inimical to the standardized norms applied in the bureaucratized education system. In his research in West Java (with Dede Syarif and Moch Fakhruroji) Millie discovered how talaqqi is regarded as an asset by pesantren. As the pesantren sector becomes more deeply dependent on the resources and protocols of the national education system, greater care is taken to structure institutional activities around talaqqi, ensuring the distinctiveness of Islamic education, and maintaining the specific institution’s authentic connection to the past through genealogy and remembrance.